Lanthanide-doped mesoporous MCM-41 nanoparticles as a novel optical–magnetic multifunctional nanobioprobe. Issue 70 (10th December 2019) - Liu, Jun; Liu, Siqian; Li, Yaling; Xue, Jiayan; He, Youyi; Liu, Fuchi; Yang, Li; Hu, Junhui; Xiong, Zhengye; Long, Lizhen
Abstract : Mesoporous Ln-MCM-41 nanoparticles with optical–magnetic dual-modal properties can be used as a multifunctional nanoprobe for application in bioseparation, optical–magnetic bioimaging, and drug delivery. Abstract : To research and develop potential multifunctional nanoprobes for biological application, lanthanide-doped MCM-41 (Ln-MCM-41, Ln = Gd/Eu) silica nanoparticles with excellent pore structure and optical–magnetic properties were synthesized via a facile and economical sol–gel method. The microstructure and pore distribution of Ln-MCM-41 nanoparticles were obviously affected by the Ln-doping. As the Ln/Si mole ratio increased, the specific surface area and total pore volume of Ln-MCM-41 nanoparticles rapidly decreased. However, the Ln-MCM-41 nanoparticles still retained the typical well-ordered mesoporous structure, and exhibited excellent drug release behavior. Moreover, the drug release rate of Ln-MCM-41 was remarkably pH-dependent and increased gradually upon decreasing pH. Additionally, these nanoparticles also exhibit considerable photoluminescence properties, living cells photoluminescence imaging in vitro, and paramagnetism behavior at room temperature due to the Ln 3+ -ions doping. Our research shows the possibility of our Ln-MCM-41 nanoparticles as multifunctional nanoprobes for application in bioseparation, bioimaging, and drug delivery.